2014
DOI: 10.1007/s00248-014-0412-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chasmoendolithic Community in Miers Valley, McMurdo Dry Valleys, Antarctica

Abstract: The Antarctic Dry Valleys are unable to support higher plant and animal life and so microbial communities dominate biotic ecosystem processes. Soil communities are well characterized, but rocky surfaces have also emerged as a significant microbial habitat. Here, we identify extensive colonization of weathered granite on a landscape scale by chasmoendolithic microbial communities. A transect across north-facing and south-facing slopes plus valley floor moraines revealed 30-100 % of available substrate was colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 53 publications
3
57
1
2
Order By: Relevance
“…A recent study of Miers Valley granite chasmoendoliths demonstrated that Leptolyngbya (Oscillatoriales) was the dominant cyanobacterial colonist (Yung et al 2014). Interestingly, the authors reported a shift from Chroococcidiopsis-like phylotypes on colder-drier slopes to Synechococcus-like phylotypes on warmer-wetter slopes.…”
Section: Hypolithsmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study of Miers Valley granite chasmoendoliths demonstrated that Leptolyngbya (Oscillatoriales) was the dominant cyanobacterial colonist (Yung et al 2014). Interestingly, the authors reported a shift from Chroococcidiopsis-like phylotypes on colder-drier slopes to Synechococcus-like phylotypes on warmer-wetter slopes.…”
Section: Hypolithsmentioning
confidence: 97%
“…The variability in the environmental factors, together with the less than ideal levels of nutrients required for biological activity, severely restrict microbial communities in polar environments. In the absence of other photoautotrophic clades, it is accepted that cyanobacteria are largely responsible for providing the most important ecosystem services, and that cyanobacterial autotrophy supports substantial and diverse populations of heterotrophic microorganisms (such as Actinobacteria, Proteobacteria, Firmicutes and Bacteroidetes) together with smaller numbers of organisms in higher trophic levels (Aislabie et al 2006;Babalola et al 2009;Chan et al 2012;Stomeo et al 2012;Makhalanyane et al 2013a;de los Rios et al 2014;Yung et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Exposed granites in the McMurdo Dry Valleys display a severe weathered surface and laminar flaking of surface layers. These are sites for chasmoendolithic colonization, and studies have shown that this is cyanobacterial with possible lichen associations (de los Rios et al 2005(de los Rios et al , 2007Yung et al 2014). The community is significantly different from surrounding soils and other lithic colonization (Yung et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Moisture content for all substrates was \2 % w/w with the exception of hyporheic samples where moisture content was [100 % w/w for all samples as measured gravimetrically in the field. At each site, triplicate samples of open soil, hypoliths (communities beneath quartz stones), chasmoendoliths (communities in rock fissures, granite in Miers Valley and sandstone in McKelvey Valley) and cryptoendoliths (communities within structural cavities of sandstone rock) as defined by Golubic et al (1981) were recovered aseptically as previously described (Pointing et al 2009;Rao et al 2011;Yung et al 2014). Samples were stored at -80 °C until processed.…”
Section: Methodsmentioning
confidence: 99%
“…These sub-surface communities account for the majority of standing biomass in desert systems (Pointing and Belnap 2012) including polar deserts (Cary et al 2010;Wierzchos et al 2012). These lithic communities are dominated by cyanobacteria and lichens, but also support a diverse range of archaea, bacteria, chlorophytes and fungi (Friedmann 1982;De La Torre et al 2003;Broady 2005;De Los Rı´os et al 2007;Wood et al 2008;Pointing et al 2009;Cowan et al 2010;Rao et al 2011;Cowan et al 2012;DeLosR´ıos et al 2014;Richter et al 2014;Yung et al 2014). Metazoan life is comparatively sparse, with limited direct evidence for grazing on microbial communities (Wall and Virginia 1999).…”
Section: Introductionmentioning
confidence: 99%